SEDIMENTASI SOSIAL DALAM TINDAKAN KESEHARIAN PENGIKUT PARMALIM, KRISTEN, DAN ISLAM DI DESA PARDOMUAN NAULI LAGUBOTI - Mispa Sulastri Tambunan; Rama Tulus Pilakoannu (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2021)
This article studies the social sedimentation in the daily actions of Parmalim, Christian, and Islam adherents in Pardomuan Nauli Village, Laguboti. The multi-religious Batak people adhere to same customs, norms, traditions and cultures. But, in preserving same customs, norms, and culture, in fact, some conflicts still appear among the people. Through social sedimentation, however, people in Pardomuan Nauli can live in harmony and unity. This study employs Erving Goffman’s theory to see the interaction among people in their daily life. It also sees how people still can live in harmony among the religious differences by using social networks theory. The objective of study is to apply the development of qualitative research design and library research. The data were collected by conducting interviews, observation, and theoretical review. This study describes and analyzes how Parmalim, Christian, and Islam people in Batak Toba tribe live up the social sedimentation in their daily lives and also, how do they preserve the cultural values they have amidst religious differences.